Perubahan Makna serta Benturan Klaim akan Ruang Kota pada Kawasan Taman Kencana Bogor - Widyawati, Karya; Suryani, Nia (RUAS, 2018)
Taman Kencana Bogor be a witness of the development of the city of Bogor from the colonial period as a residential area for researchers and government employees. Since the development of Bogor this area has drastic changes. Utilization of buildings as a place of business has changed the structure of many urban space. In addition, the more famous Taman Kencana as a culinary tourist point in Bogor also gives impact to this place. To reveal the impact of the development of this region, conducted with qualitative data collection, archival research, and interviews and observations on a regular basis. This situation also indicates a relationship ofÂ attraction between the interests of the function area as a residential area and culinaryÂ tourism, and there was a clash of claims to space.